2009
DOI: 10.1007/s11095-009-9961-8
|View full text |Cite
|
Sign up to set email alerts
|

The Antiepileptic Drug Topiramate is a Substrate for Human P-glycoprotein but Not Multidrug Resistance Proteins

Abstract: Thus, these data indicate that brain levels of topiramate may be affected by overexpression of Pgp as determined in patients with intractable epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…When 1,25(OH) 2 D 3 is used in combination with anticancer agents such as paclitaxel, a known P-gp substrate, to treat cancer (Masuda and Jones, 2006), lower therapeutic effects may result in the brain. P-gp substrates targeting the brain include the antiretrovirals such as atazanavir, ritonavir, and jpet.aspetjournals.org saquinavir for HIV treatment, antipsychotics such as risperidone (Kim, 2002;Zastre et al, 2009), antiepileptic drugs such as topiramate (Luna-Tortós et al, 2009), or central nervous system drugs such as morphine (Groenendaal et al, 2007), and all of these probably will be affected. On the other hand, increased P-gp activity may decrease brain concentration of a drug such as oseltamivir (Tamiflu), a drug used for influenza treatment, which is a P-gp substrate (Morimoto et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…When 1,25(OH) 2 D 3 is used in combination with anticancer agents such as paclitaxel, a known P-gp substrate, to treat cancer (Masuda and Jones, 2006), lower therapeutic effects may result in the brain. P-gp substrates targeting the brain include the antiretrovirals such as atazanavir, ritonavir, and jpet.aspetjournals.org saquinavir for HIV treatment, antipsychotics such as risperidone (Kim, 2002;Zastre et al, 2009), antiepileptic drugs such as topiramate (Luna-Tortós et al, 2009), or central nervous system drugs such as morphine (Groenendaal et al, 2007), and all of these probably will be affected. On the other hand, increased P-gp activity may decrease brain concentration of a drug such as oseltamivir (Tamiflu), a drug used for influenza treatment, which is a P-gp substrate (Morimoto et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Luna-Tortós et al (110) pointed out that conventional bidirectional transport assays may not be suitable to identify ASDs as P-gp substrates due to the highly permeable nature of most ASDs. Using a modified transport assay (concentration equilibrium transport assay; CETA) which allows evaluating active transport separately from passive permeability, Luna-Tortós et al detected P-gp transport of phenytoin, phenobarbital, lamotrigine, levetiracetam, and topiramate, but not carbamazepine in MDR1-transfected LLC-PK1 cells (110, 111). Zhang et al (101) used both the cell monolayer bidirectional assay and CETA in MDR1-transfected MDCKII and LLC-PK1 cells to test if phenytoin, phenobarbital, or ethosuximide were transported by P-gp.…”
Section: Potential Mechanisms Of Asd Resistancementioning
confidence: 99%
“…Using CETA in MDCKII kidney cells transfected with human MRP1, MRP2, or MRP5, Luna-Tortós et al reported that none of the ASDs tested (topiramate, valproate, carbamazepine, phenytoin, levetiracetam, lamotrigine, and phenobarbital) was transported by any of those MRPs (111, 112). In vivo studies may be needed to confirm the findings from in vitro experiments, but few clinical studies have focused on studying the relationship between ASDs and MRPs.…”
Section: Potential Mechanisms Of Asd Resistancementioning
confidence: 99%
“…In addition, administration of TPM in patients already taking phenytoin twice a day, a 25% rise in the concentrations of phenytoin were found and may require a downward adjustment of phenytoin dosage (47). Besides in patients with pharmacoresistant epilepsy, Luna-Tortos et al (2009) (48) provided evidence that brain levels of topiramate may be affected by overexpression of P-glycoprotein. Enhanced elimination of TPM was also observed during pregnancy.…”
Section: Antiepileptic Drugs (Structures See Figure 2)mentioning
confidence: 99%